2014
DOI: 10.1684/epd.2014.0648
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric epilepsy surgery in the posterior cortex: a study of 62 cases

Abstract: Past surgical series have emphasized the diagnostic complexity of posterior cortex epilepsy. Available data are sparse, especially in children, and most published series report a high number of surgical failures and post‐operative neurological deficits. In this article, we present a paediatric cohort of 62 children who underwent surgery for drug resistant posterior cortex epilepsy before the age of 16 years with a mean post‐operative follow‐up of 6.94 years (range: 2–16). Mean age at epilepsy onset was 3.2 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 47 publications
(103 reference statements)
2
58
1
10
Order By: Relevance
“…Our study showed that scalp EEG monitoring is often misleading or non‐localizing in patients with PLE. This finding has also been observed in previous studies (Cascino et al ., ; Salanova et al ., ; Kim et al ., ; Binder et al ., ; Bartolomei et al ., ; Liava et al ., ; Francione et al ., ) ( table ). Interictal and ictal scalp EEG recordings in patients with PLE have lower localizing value compared with temporal lobe epilepsy patients (Ristic et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study showed that scalp EEG monitoring is often misleading or non‐localizing in patients with PLE. This finding has also been observed in previous studies (Cascino et al ., ; Salanova et al ., ; Kim et al ., ; Binder et al ., ; Bartolomei et al ., ; Liava et al ., ; Francione et al ., ) ( table ). Interictal and ictal scalp EEG recordings in patients with PLE have lower localizing value compared with temporal lobe epilepsy patients (Ristic et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other aura types, including those often attributed to other lobes ( e.g . epigastric aura), could be seen in patients with PLE (Tufenkjian and Lüders, ; Liava et al ., ; Francione et al ., ). There is no pathognomonic clinical manifestation in patients with PLE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liava et al 25 described 62 children with DRE and focal seizures from the posterior cerebral cortex, including 24 patients in whom SEEG facilitated localisation of the epileptogenic zone. Among patients who underwent SEEG, 75% achieved seizure freedom.…”
Section: Stereotactic Eegmentioning
confidence: 99%
“…This patient is a typical example of what has been described as pseudo‐temporal epilepsy, in which seizures start in extra‐temporal lobe structures and later spread over the temporal lobe region, therefore mimicking temporal semiology (Andermann, ). Extra‐temporal lobe regions include the orbito‐frontal cortex (Shihabuddin et al ., ), the insula (Isnard et al ., ), and the parieto‐occipital regions (Williamson et al ., ; Palmini et al ., ; Liava et al ., ; Francione et al ., ), especially the posterior cingulate (Devinsky et al ., ; Alkawadri et al ., ; Enatsu et al ., ). Alkawadri et al .…”
Section: Invasive Investigationmentioning
confidence: 99%